RIUNGAN: REPRESENTATION OF MUSLIM BETAWI PINGGIR THROUGH THE PRACTICE OF EATING TOGETHER (A CASE STUDY OF KAMPUNG PONDOK PUCUNG, PONDOK AREN, SOUTH TANGERANG) - Julianto, Gregorio Surya Abdi; Bachrioktora, Yudi (International Review of Humanities Studies, 2024)
Riungan is an eating-together event involving the kampung community as a form of religious worship and gratefulness/gratitude to God. Through an ethnography approach, with in-depth interviews and a literature review as a method, this research explores the relationship between the practice of eating together and cultural identity in riungan as held by the Muslim Betawi of Kampung Pondok Pucung. The result of this research shows that riungan has become a space to representation of the cultural identity of the Betawi Pinggir (peripheral Betawi), particularly emphasizing their cultural and Islam heritage. Through the types of food brought and the communal eating practices, the cultural identity influenced by Sundanese and Javanese cultures is revealed. The practice of riungan at the mosque, musalla, and residents' homes underscores that this food practice is not only a form of worship but also a means to strengthen social relationships within the Muslim community, thereby reinforcing their cultural and religious identity.